Beyond rhetoric: re-thinking entrepreneurial marketing from a practice perspective. Issue 2 (14th October 2014) - Gross, Nicole; Carson, David; Jones, Rosalind
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose the application of social practice theory for the investigation of entrepreneurial marketing (EM) practices. Design/methodology/approach – A theoretical gap has been found between scholarly efforts to explain the nature of EM practice and the actual marketing practice or marketing doings of small firms. Findings – The paper covers some of the EM literature and perspectives and examining the notion of "practice" in small- and medium-sized enterprises (SME) and entrepreneurship research. Based on an increasing focus on practice in the social theory literature and the contributions of key social theorists, a discussion is framed in terms of how EM practice can be studied through the investigation material and bodily observations and common interpretations. Research limitations/implications – The paper offers a proposal that the observations of practitioners' actions and activities and the investigation of common interpretations can be conceptualized to explain the nature of EM practice. It also gives avenues for future research. Practical implications – The paper suggests that marketing comprises a wide scope of activities or practices and, in the case of a small firm, is all-pervasive. It also suggests that scholars engage in understanding the collective, distributed, situated, ongoing and tacit nature of EM. Originality/value – The paper provides a fresh conceptual approach about how EM practice can be studied through the investigation material and bodily observations as well as common interpretations.